Development of a Swelling Model for Strong Expansive Soil Under K0 Stress State for Building Foundation Applications - Shuangping Li; Bin Zhang; Han Tang; Zuqiang Liu; Junxing Zheng (Buildings, 2025)
This study explores the swelling behavior of strong expansive soil from the Nanyang Section II canal bed of the South-to-North Water Diversion Middle Route Project, with practical relevance to foundation engineering. A total of 45 one-dimensional swelling tests were performed using a lever-type consolidation apparatus under K0 stress conditions. The test matrix covered three dry densities (1.45, 1.50, and 1.55 g/cm3), three initial moisture contents (20%, 25%, and 30%) and five overburden pressures (0, 12.5, 25, 50, and 100 kPa). Results indicated that the swelling rate decreased in a logarithmic pattern with increasing pressure and was strongly influenced by compaction level and initial moisture. The highest observed swelling rate was 14.96% under zero loading. Based on the experimental data, a semi-empirical model was developed that accounts for dry density, water content, and overburden pressure. The model showed strong agreement with the test results (R2 = 0.9888) and was further validated using an independent dataset (dry density = 1.60 g/cm3), achieving R2 = 0.981 and RMSE = 0.606%. The proposed model serves as a practical tool for predicting swelling-induced deformation and supports engineering decisions on compaction, moisture conditioning, and foundation stability in expansive soil regions.